Synthesis of Biopositive Composites Based on Gypsum Binder and Dispersed Additive of Unburned Coal - Victoria Petropavlovskaya; Kirill Petropavlovskii; Tatiana Novichenkova; Yury Kosivtsov; Mikhail Sulman (Chemical Engineering Transactions)
Reducing the density of building composites improves a number of performance properties of materials. Reducing the thermal conductivity, weight, and thickness of building products provides a solution to problems of energy and resource conservation and leads to a reduction in the consumption of natural resources and energy. To solve these problems, the work explores the possibility of using one of the fractions of fuel ash containing predominantly unburned organic residues of solid fuel. The structural features of unburned coal after high-temperature treatment can contribute to the transformation of the structure of mineral composites. The synthesis of modified gypsum with the addition of unburned coal fraction additionally leads to a reduction in the volume of gypsum binder used by up to 30 %. The purpose of the work was to determine the optimal additive content of this by-product according to the criteria of density and porosity. The results obtained demonstrate the effect of changing the content of additives on the synthesis of modified gypsum. It has been established that gypsum modified is superior to the control composition in all aspects of structural changes. First of all, this was manifested in the porosity characteristics. The radical change in the pore structure is confirmed by research and analysis of the results obtained using the mercury porosimetry method. The total pore volume increased more than 4 times. The achieved results on density and porosity open up new broad opportunities in the field of creating bio-positive materials for green construction.